A necessary reform of agriculture market access rules. Issue 2 (30th June 2020) - Eba Nguema, Ismaelline
Abstract : Purpose: The purpose of this paper is to demonstrate by text and empirical facts, the need to reform the rules in force. Design/methodology/approach: This study confronts current standards with empirical facts. To do this, it is postulated that even though current market access standards are better that the Gatt 1947 rules, they leave the possibility for some members to hijack them to eventually increase their protection effective tariff. Findings: Market access standards for agricultural products should be reformed because of their asymmetry. To put an end to this asymmetry, these standards should be rebalanced. This is precisely the challenge of the current multilateral negotiations. Originality/value: Unlike the studies conducted on this subject (to my knowledge), which are mainly based on economic or political science methods, this analysis is essentially based on legal reasoning law.